HEMOROİDLERİN MEDİKAL TEDAVİSİ - ERSAN, Yılmaz; YAVUZ, Nihat; ERGÜNEY, Sabri; KUŞASLAN, Ramazan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Better understanding of the pathophysiology and anatomy of the anal canal has added to increased success in the treatment of hemorrhoids. Current therapies of hemorrhoids are: 1. Conservative/medical management, 2. Non excisional invasive therapy, 3. Surgical treatment. The choice of treatment methods depends on the severity and type of symptoms, the degree of prolapse, the expertise of the surgeon and equipment available. Conclusion.- Medical management of the hemorrhoids can be accomplished in the majority of patients. Therapy options vary from advice with respect to defecation habits, dietary manipulations and local hygien, oral vasotopic drugs and topical agents. However, there is still much discussion about pharmacological treatment of certain symptoms caused by hemorrhoids and their complications. The aim of this study is to assess the role of medical treatment of hemorrhoids.